On the postulation of lines and a fat line. (March 2019) - Bauer, Thomas; Di Rocco, Sandra; Schmitz, David; Szemberg, Tomasz; Szpond, Justyna
Abstract: In the present note we show that the union of r general lines and one fat line in P 3 imposes independent conditions on forms of sufficiently high degree d, where the bound is independent of the number of lines. This extends former results of Hartshorne and Hirschowitz on unions of general lines, and of Aladpoosh on unions of general lines and one double line.